The Initial Response to the Boston Marathon Bombing: Lessons Learned to Prepare for the Next Disaster - Gates, Jonathan D. (Ann Surg, 2014)
OBJECTIVE: We discuss the strengths of the medical response to the Boston Marathon bombings that led to the excellent outcomes. Potential shortcomings were recognized, and lessons learned will provide a foundation for further improvements applicable to all institutions. BACKGROUND: Multiple casualty incidents from natural or man-made incidents remain a constant global threat. Adequate preparation and the appropriate alignment of resources with immediate needs remain the key to optimal outcomes. METHODS: A collaborative effort among Boston’s trauma centers (2 level I adult, 3 combined level I adult/pediatric, 1 freestanding level I pediatric) examined the details and outcomes of the initial response. Each center entered its respective data into a central database (REDCap), and the data were analyzed to determine various prehospital and early in-hospital clinical and logistical parameters that collectively define the citywide medical response to the terrorist attack. RESULTS: A total of 281 people were injured, and 127 patients received care at the participating trauma centers on that day. There were 3 (1%) immediate fatalities at the scene and no in-hospital mortality. A majority of the patients admitted (66.6%) suffered lower extremity soft tissue and bony injuries, and 31 had evidence for exsanguinating hemorrhage, with field tourniquets in place in 26 patients. Of the 75 patients admitted, 54 underwent urgent surgical intervention and 12 (22%) underwent amputation of a lower extremity. CONCLUSIONS: Adequate preparation, rapid logistical response, short transport times, immediate access to operating rooms, methodical multidisciplinary care delivery, and good fortune contributed to excellent outcomes.